Computer-based Role Playing Game Environment for Analogue Electronics - Graven, Olaf Hallan; Samuelsen, Dag; MacKinnon, Lachlan M (International Journal of Online and Biomedical Engineering (iJOE), 2009)
An implementation of a design for a game based virtual learning environment is described. The game is developed for a course in analogue electronics, and the topic is the design of a power supply. This task can be solved in a number of different ways, with certain constraints, giving the students a certain amount of freedom, although the game is designed not to facilitate trial-and-error approach. The use of storytelling and a virtual gaming environment provides the student with the learning material in a MMORPG environment.